122 Systematic review of costs and cost-effectiveness of treatment for relapsed/refractory acute leukaemia in children. (18th July 2022) - Soliman, Ranin; Heneghan, Carl; Bolous, Nancy; Sidhom, Iman; Ahmed, Sonia; Roberts, Nia; Oke, Jason; Elhaddad, Alaa
Abstract : Objectives: Novel treatments have been developed for relapsed/refractory (r/r) acute leukaemia in children, yet limited evidence exists about the most cost-effective strategies. In this review, we summarized the evidence about costs and cost-effectiveness of treatment for r/r acute leukaemia in children, and compared costs and effects of alternative treatment interventions. Method: We conducted a systematic literature search in Medline, Embase, Cochrane Database, and other health economic databases, from inception until August 13th, 2021. We summarized key economic approaches, costs (actual and adjusted to USD 2019), clinical outcomes (quality-adjusted life-years (QALYs), survival), and incremental cost-effectiveness ratios for main interventions and comparators. Quality appraisal was conducted using the CHEERS checklist. Results: We included 12 eligible studies, of which ten evaluated the costs/cost-effectiveness of CAR-T cell therapy for r/r pediatric acute lymphoblastic leukemia (ALL). CAR-T cell (tisagenlecleucel) was cost-effective compared to other interventions, followed by Blinatumomab, and Clofarabine therapy, whereas FLA-IDA salvage chemotherapy (with/without stem cell transplant (SCT)) provided the least value for money. Bone marrow transplant was more cost-effective than peripheral blood SCT for standard-risk pediatric acute leukemia. Levofloxacin prophylaxis was cost-saving during intensive chemotherapy for relapsed ALL and acute myeloid leukemia (AML). However, there was limited published articles about the cost/effectiveness of r/r AML treatments. Conclusions: CAR-T cell therapy is the primary candidate in treating r/r ALL, yet, there remain serious concerns over uncertainty of its long-term effectiveness, affordability of drug price, and equity in access to resource-limited settings. The quality of generated evidence is moderate to high, with limited generalizability of findings due to high variability in outcomes obtained from modelling studies. The generated evidence will help clinicians make better informed decisions to adopt the most cost-effective and affordable treatment(s) for r/r ALL. We present evidence-based recommendations to provide cost-effective treatment in real-world contexts, with implications for healthcare policy and practice.